Inter-firm R&D cooperation in local innovation networks: The case of Italian technological districts - Otello Ardovino; Luca Pennacchio (Economics and Econometrics Research Institute (EERI), 2014)
This paper explores the drivers of inter-firm R&D collaborations in a particular type of innovation network, the technological districts created in Italy under a specific public policy to promote innovation. The empirical analysis used an original database containing information on research projects activated by the districts and on the characteristics of participating firms. The main results show that districts with governance oriented towards market logic and districts that include several universities foster a stronger cooperation among firms than other districts. In addition, network effects such as structural embeddedness and interlocking directorate greatly influence the propensity to cooperate. Lastly, knowledge transfer and absorptive capacity of firms also play an important role in shaping collaboration strategies. Some considerations about the effectiveness of public policy also emerge from the analysis. In particular technological districts foster research collaborations among small firms and between small and large firms. The latter type of cooperation could be very important to enhance the innovation capabilities of small firms and their performance.
Keywords: L14; O31; O32; 330; R&D cooperation; innovation networks; firm behaviour; dyadic regession